Efektivitas Sabun Cuci Tangan Ekstrak Daun Afrika ( Vernonia amygdalina Del.) Terhadap Bakteri Escherichia coli - Panji Ratih Suci; Cikra Ikhda Nur H.S; Anita Candra Ningtyas; Annisa Lailatul Maghfiroh (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
African leaf plants (Vernonia amygdalina Del.) is one of tradisional medicine and has pharmacological contain secondary metabolite such as Flavonoids, Saponin, Tanin and Alkaloid. This study aimed to determine the antibacterial activity of African leaf extract (Vernonia amygdalina Del.) in handsoap formulation on the growth of Escherichia coli. African left extract was obtained from maceration process with ethanol and phytochrmical screening was carried out.This study uses concentration of 0,5%, 1% and 2%. Antibacterial activity testing using scratch and disc diffusion methods. Tis study also evaluated the pyshical quality of the preparation which included organoleptic observation, homogeneity test, high foam test and antibacterial activity test. Antibacterial activity testing using scratch and disc disfusion methods. African pyctochemical screening was carried out. The result showed that the percentage of African leaf extract yield was 24,958%. The pH test gets a pH of 10-11 and 5-6 cm foam height test. The highest concentration of positive control of preparation containing alcohol (Dettol) with an average number og 4,72 mm ± 1,45 mm. Liquid soap preparation 1% with a diameter of inhibition of 3,93 mm ± 1,97 mm. The result of this study inhibit the growth of Eshcherichia coli bacteria.